Investigation of optimum EDM die sinking parameters in micro dimple machining - Lee, Jie Ying; Ahmad Rosli, Abdul Manaf (Penerbit UMP, 2022)
Micro dimple is a standard surface structure that is commonly used in micro-moulds, micro/nano-fluid devices, micromechanical systems, and bionic functional surfaces. These microstructure surfaces can be used for optical communication systems, micro sensors, flat panel display, light emitting diode applications and others. Many researchers have performed investigations on the parameters that help in manufacturing the micro dimple. However, there is still limited research on the certain parameters that will affect the micro dimple using EDM die sinking machine. EDM die sinking process involved a tool and workpiece material which immersed in a dielectric fluid medium and use the electrical spark discharges from electric pulse generation to remove the workpiece material. The actual performance of the surface integrity and form accuracy in micro dimple by EDM die sinking machine remains unclear. Therefore, this research attempts to investigate the effect of the dimple measurement such as diameter, depth and surface roughness (Ra) to the parameters which is surface roughness (Rz), sparking gap and type of electrode. By utilising the parameters, the lab experiment was conducted, and their surface integrity, effects in micro dimple behaviour were investigated. It was discovered that the higher surface roughness (Rz), the higher current produced thus erodes the material and caused the measurement of the dimple (diameter, depth and surface roughness (Ra)) differed from the expected size. Also the findings that the surface integrity was ununiformed due to the tool worn out occurred during the electric spark process causing high material rate removal. Other than that, the material electrode which has the high thermal conductivity and melting point resulted the best form accuracy of micro dimple.